2014
DOI: 10.1016/j.nicl.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging abnormalities in idiopathic generalized epilepsy

Abstract: Magnetic resonance imaging (MRI) techniques have been used to quantitatively assess focal and network abnormalities. Idiopathic generalized epilepsy (IGE) is characterized by bilateral synchronous spike–wave discharges on electroencephalography (EEG) but normal clinical MRI. Dysfunctions involving the neocortex, particularly the prefrontal cortex, and thalamus likely contribute to seizure activity. To identify possible morphometric and functional differences in the brains of IGE patients and normal controls, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 42 publications
5
30
0
Order By: Relevance
“…Routine magnetic resonance imaging (MRI) is normal in IGE individuals [2]. However, quantitative neuroimaging methods have identified several regional abnormalities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Routine magnetic resonance imaging (MRI) is normal in IGE individuals [2]. However, quantitative neuroimaging methods have identified several regional abnormalities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, NOE patients also showed significantly elevated fALFF in all the subcortical and cortical brain regions for the slow‐3 subband relative to healthy controls. This observation includes the default mode network areas, which corresponds to the effects previously reported on idiopathic generalized epilepsy using the fALFF measure …”
Section: Discussionmentioning
confidence: 64%
“…An anatomic atlas that divides the brain into 70 regions based on the gyri and sulci was calculated . A number of studies using fMRI on epilepsy motivated us to define the regions of interest (ROIs), including the thalamus, hippocampus, temporal cortex, prefrontal cortex, precentral cortex, postcentral cortex, posterior cingulate cortex, inferior parietal cortex, precuneus, and occipital cortex …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations